Competitive swimming relay exchange times: A descriptive study - Siders, W. (International Journal of Sports Science and Coaching, 2010)
Relay exchange times have been proposed as a training target to improve final placing in swimming competition. This study investigated that possibility by analyzing relay exchange times from the 2007 and 2008 USA NCAA Divisions I and II Swimming and Diving Championships. Exchange times from 1292 teams competing in 200 and 400 yard free and medley and 800 yard free relays were studied. The mean team exchange time for non-disqualified teams was .746 ± .232 (standard deviation) sec. Finish places were improved by faster relay exchange times for 205 (15.8% of 1292) teams - exchange times were faster than the next placing team by a time equal to or more than the difference in final times. It is recommended that swimming relay training include strategies to optimize exchange time. However, coaches and competitors must carefully weigh benefits against risks - 3.1% of the teams were disqualified for early relay take-offs.